The Influence of Classroom Flipped Model and Heuristic Vee on Students' Understanding of Mathematical Concepts - Syahrul, Muhammad; Kalsum, Ummu; Putri, Cindi Nadya; Mardiyana, Lilis; Sutduean, Jutamat (Desimal: Jurnal Matematika, 2020)
We already know that, there are many learning models that are used to improve the ability to understand mathematical concepts. In this study, researchers will use two learning models that have been previously studied. But this study is different from previous studies, this study aims to find a better model in improving the ability to understand students' mathematical concepts through test results by applying the flipped classroom and heuristic vee models. The method used in this study is quasi-experimental (quasi-experimental) and testing using the T and N-Gain test. Based on the results of the data analysis conducted, it can be concluded that increasing the ability to understand mathematical concepts of students who use the flipped classroom learning model is far better than vee heuristics.